Efektifitas Teknologi Informasi dalam Proses Belajar Mengajar pada Universitas Budi Luhur - Spits Warnars Harco Leslie Hendric (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2006)
In general, however, IT will empower students to have greater control over the learning process, with all the benefits associated with active learning and personal responsibility. Not only will students decide when to learn and how to learn, increasingly they will also decide what to learn and how that learning is to be certified. Traditionally, higher education institutions have combined several functions in their faculty. Faculty are architects as they design learning programs; navigators as they help advise students in their course of study; instructors when they lecture; mentors when they help students form a sense of connectedness to the world; and evaluators and certifiers as they decide to grant students grades or degrees.Keywords: learning process, active learning, higher education